2007
DOI: 10.1007/bf03175067
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of solid paraffin (C11−40) byPseudomonas aeruginosa MGP-1

Abstract: Isolated from oil-contaminated soil, Pseudomonas aeruginosa strain MGP-1 was identified by 16S rDNA sequence analysis and phenotypic characterisation. This strain was highly competent in medium and in soils, grew and survived well under adverse conditions. MGP-1 did not produce the pathogenic factor pyocyanin and used paraffin (C 11-40 ) as sole carbon source. It degraded eicosane (C 20 ) more efficiently than other n-alkanes, removing 60% within 16 days. An alkB gene and intermediate metabolites of mono-alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As far as we know, there are no previous works exploring the differences in the bacterial communities induced by this set of n-alkanes. However, it is important to note that in a study where the degradation capacity of n-alkanes was studied using a bacterial strain isolated from contaminated soil (Pseudomonas aeruginosa MGP-1), Salgado-Brito et al (2007) reported that the growth rate and degradation capacity of this strain were optimal with the n-alkane of C20, and decreased when the length of the carbon chain was larger o shorter. These authors clearly show that growth rate of the MGP-1 strain was notoriously low with C11 and gradually increases with C12, C13 and C14.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there are no previous works exploring the differences in the bacterial communities induced by this set of n-alkanes. However, it is important to note that in a study where the degradation capacity of n-alkanes was studied using a bacterial strain isolated from contaminated soil (Pseudomonas aeruginosa MGP-1), Salgado-Brito et al (2007) reported that the growth rate and degradation capacity of this strain were optimal with the n-alkane of C20, and decreased when the length of the carbon chain was larger o shorter. These authors clearly show that growth rate of the MGP-1 strain was notoriously low with C11 and gradually increases with C12, C13 and C14.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that Pseudomonas are capable of degrading n-alkanes longer than C 20 (up to C 40 ) (Gunasekera et al 2013;Liu et al 2014;SalgadoBrito et al 2007;Yuste et al 2000). Salgado-Brito et al measured the degradation kinetics of Pseudomonas aeruginosa MGP using paraffin (C 11 -C 40 ) as sole carbon source (Salgado-Brito et al 2007). They found that this strain degraded eicosane (C-20) more efficiently than other n-alkanes, removing 60 % within 16 day.…”
Section: Changes In Oil Concentration and Composition During Bioaugmementioning
confidence: 97%
“…These three genera contained many hydrocarbon degraders that were commonly found in terrestrial environments. Genus Pseudomonas includes many species that are commonly associated with the biodegradation of petroleum hydrocarbons (Lee et al 2010;Salgado-Brito et al 2007;Whyte et al 1997). Genus Nocardia are aerobic and Gram-positive actinomycetes that are widely distributed in aquatic and terrestrial environments.…”
Section: Isolation and Characterization Of Oil-degrading Strainsmentioning
confidence: 98%